Crystal structure and XANES study of Fe-substituted Barium Titanate ceramics prepared by conventional solid-state technique. (November 2021) - Padchasri, J.; Triamnak, N.; Sareein, T.; Jutimoosik, J.; Tongsaeng, S.; Bootchanont, A.; Kidkhunthod, P.; Rujirawat, S.; Manyum, P.; Yimnirun, R.
Abstract: The structural characterizations of Fe-substituted Barium Titanate (Fe–BaTiO3 ) ceramics prepared at different sintering temperatures were investigated in this work. The Fe–BaTiO3 ceramics (with 10 mol% of Fe substitution) were prepared via a conventional solid-state reaction (SSR) method. The structural data were examined by XRD (X-ray Diffraction) and XAS (X-ray Absorption Spectroscopy) techniques. The results revealed the transformation from tetragonal to hexagonal structure with increasing sintering temperature. The measured XANES (X-Ray Absorption Near-Edge Structure) data exhibited the oxidation state of Fe ion as Fe 3+ in the Fe–BaTiO3 . The comparison between measured and calculated XANES spectra to examine the effect of different sintering temperatures on the local structure around the Ti atom was carried out. Finally, it should be emphasized that the local structure evolution in Fe–BaTiO3 ceramics may be explored by the XANES investigations. Highlights: Sintering Temp. Affects BTO structural change from mixed tetra-hexagonal to hexagonal structure. XRD and XANES were used to reveal the global and local structure of the doped samples. Ti K -edge XANES confirmed the local structure transition around Ti.